From State Sovereignty To People Sovereignty: The Development of State Control Doctrine in Indonesia Constitutional Court Decision - Utia Meylina (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
State Control Doctrine in Indonesia has no restriction criteria. The high of rights granted by the constitution to make the state the power to the state's enormous power in respect of Article 33 of the Constitution of 1945. The absence of this restriction criteria led to the state capable of acting arbitrarily, it is at the reflection of the enactment of state sovereignty. Democracy continues to grow until delivery of the Constitutional Court. Through the decisions of the Constitutional Court this is slowly becoming a limiting criterion State Control Doctrine in Indonesia. Former power in the hands of the state slowly began to shift into the hands of the public. By analyzing the decision of the Constitutional Court will be able to describe the shift towards state sovereignty tipeople  sovereignty.